Materials Engineering Strategies to Control Metal Oxides Nanowires Sensing Properties (Adv. Mater. Interfaces 12/2022). Issue 12 (22nd April 2022) - Kaur, Navpreet; Singh, Mandeep; Comini, Elisabetta
Abstract : Metal Oxides Nanowires Metal oxides nanowires modification strategies such as branched‐like heterostructure, decoration with metal/metal oxide particles, core‐shell structures, surface functionalization with self‐assembled monolayers etc. are reported to improve their sensing performance especially selectivity, response, and operating temperatures, as reviewed in article number 2101629 by Navpreet Kaur, Mandeep Singh, and Elisabetta Comini.